Ronald Freedman (compilador). La revolución demográfica mundial. México ; Editorial UTEHA, 1966. 358 p. - Morelos, José B. (Estudios Demográficos y Urbanos, 1967)
RONALD FREEDMAN (compilador). La revolución demográfica mundial. México, Editorial UTEHA, 1966.